Observatoire des journalismes francophones (OJF). An online agora for French-speaking meia researchers, practitioners and their audiences - (:unkn) unknown (My University, 2025)
Journalism worldwide has been undergoing deep transformations due to the increasing prevalence of networked communications, pressure on profitability of media outlets and various scandals or never-ending debates regarding journalists’ obligations, their real or alleged failures, their presence or absence. These debates are influenced by strong expectations and a notable lack of awareness of the realities in the information world. The relationship between scholarship and journalism has a particular history of tensions, a seemingly inevitable hiatus between media scholarship and journalistic practice, generating debate that spans beyond both parties to include all citizens, thereby creating an obvious need for an agora, a place to discuss thismisunderstood profession, one which is widely recognized as being of public interest. This project has created an online agora, the “Observatoire des journalismes francophones – (http://fr.ejo.ch/)” (working title), which will serve as a meeting point for fostering discussion between different media professionals, academics and the public (citizens) at large. The Academy of Journalism and Media (AJM) of the University of Neuchâtel positions itself at the crossroads between theory and practice in journalism, training future journalists from Switzerland and abroad. Through its activities, the AJM has developed an extensive and dynamic network of educators formed of practitioners and media scholars, hailing mainly from Switzerland, Belgium and France. As such, this challenge is perfectly aligned with the mission of the AJM.
Keywords: journalism; popular science; Agora; website; publishing